Pengaruh Budaya Organisasi Dan Komunikasi Terhadap Kinerja Karyawan Mcdonald’s Cabang Kemang - Dinda Aulia Ramadhanti; Ichwan Nugroho (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
. In this era of globalization, companies are required to always optimize their human resources. Based on the power obtained by researchers, it shows that the existing culture in the company and company communication is not good. The purpose of this study was to determine the effect of organizational culture and communication on employee performance at Mcdonald's Kemang branch both partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample in this study totaling 75 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The result of this study is that organizational culture has a significant effect on employee performance, with a regression equation Y = 8,294 + 0.758X1 and a correlation coefficient value of 0.753, indicating a strong relationship. The contribution of its influence is 56.8%, while 43.2% is influenced by other factors. Hypothesis testing shows t count> t table (9.791> 1.666), so H0 is rejected and H1 is accepted. Furthermore, communication also has a significant effect on employee performance, with a regression equation Y = 4,131 + 0.853X2 and a correlation coefficient of 0.816, indicating a strong relationship. The contribution of the effect is 66.5%, while 33.5% is influenced by other factors. Hypothesis testing shows t count> t table (12.046> 1.666), so H0 is rejected and H2 is accepted. Simultaneously, organizational culture and communication have a significant effect on employee performance, with a regression equation Y = 1.605 + 0.361X1 + 0.591X2 and a correlation coefficient of 0.855, indicating a very strong relationship. The contribution of the effect is 73.1%, while 26.9% is influenced by other factors. Hypothesis testing shows F count> F table (97.927> 3.124), so H0 is rejected and H3 is accepted